A Review on Recent Advances in Aloperine Research: Pharmacological Activities and Underlying Biological Mechanisms - Zhou, Haifeng; Li, Junyi; Sun, Fei; Wang, Faxi; Li, Mingyue; Dong, Yalan; Fan, Heng; Hu, Desheng (Frontiers in Pharmacology, 2020)
Aloperine, a quinolizidine-type alkaloid, was first isolated from the seeds and leaves of herbal plant, Sophora alopecuroides L. Empirically, Sophora alopecuroides L. is appreciated for its anti-dysentry effect, a property that is commonly observed in other Sophora Genus phytomedicines. Following the rationale of reductionism, subsequent biochemical analyses attribute such anti-dysentry effect to the bactericidal activity of aloperine. From then on, the multiple roles of aloperine are gradually revealed. Accumulating evidence suggests that aloperine possesses multiple pharmacological activities and holds a promising potential in clinical conditions including skin hyper-sensitivity, tumor and inflammatory disorders etc.; however, the current knowledge on aloperine is interspersed and needs to be summarized. To facilitate further investigation, herein, we conclude the key pharmacological functions of aloperine, and most importantly, the underlying cellular and molecular mechanisms are clarified in detail to explain the functional mode of aloperine.